ASPEK PERPAJAKAN DALAM PRAKTIK TRANSFER PRICING - Harimurti, Fadjar (Universitas Slamet Riyadi, 2007)
ABSTRACT Economic globalization have brought impact progressively the increasing of international transaction or cross border transaction. Goods current, people, service, and investment have come to collapsible duplicate. In this time movement of fund and capital from one state to other state become bigger than previously. In multinational environment, happened various transaction between member covering sale of service and goods, rights license and other intangible assets, ready of loan etcetera. Price picking to the various transaction between the corporation member recognized with the title transfer pricing. Practice of this transfer pricing before now is only done by company solely just for assessing performance between company division or member, but along with practice epoch growth of transfer pricing often also be wearied for the management of tax that is a effort for the minimization of the amount of tax which must be pay. The purpose of the transfer pricing finance data transmission among company divisions or departments when them using each other service and goods one another. Besides the target also used to evaluate division performance and motivate seller division manager and buyer division to compatible decision with a purpose to company as a whole Keywords: economic globalization, transfer pricing, tax